Problems of follicular thyroid carcinoma diagnostics - S. E. Titov; S. A. Lukyanov; S. V. Sergiyko; Yu. A. Veryaskina; T. E. Ilyina; E. S. Kozorezov; S. L. Vorobyov (Опухоли головы и шеи)
Introduction. Follicular thyroid cancer is much less common than papillary cancer. Nevertheless, the main difficulties in preoperative diagnosis are associated with this morphological type. A fine needle aspiration biopsy is not able to distinguish a benign follicular adenoma from a follicular carcinoma, which forces surgeons to perform diagnostic resection of the thyroid gland in all patients with a cytological conclusion «follicular tumor».Aim. To search for microRNAs specific to follicular cancer by sequencing a new generation.Materials and methods. The data of patients with a preoperative cytological conclusion «follicular tumor» operated at the Chelyabinsk Center for Endocrine Surgery from 2021 to 2022 were analyzed. Histological preparations were reviewed twice by pathologists. Genome sequencing was performed in 8 histological samples of follicular cancer and 8 samples of follicular adenoma. The expression levels of the selected microRNAs were compared with 198 archived cytological samples of various types of thyroid tumors.Results. The risk of malignancy at the cytological conclusion «follicular tumor» was 25.4 % (error 74.6 %). Follicular cancer was first detected in 36 patients, the incidence was 0.68 new cases per 100 thousand population per year. The diagnosis of «follicular cancer» was confirmed by 3 morphologists in 8 (36.4 %) cases. Sequencing revealed the 5 most distinct microRNAs between follicular cancer and follicular adenoma: miR-625, miR-323a, let-7a, let-7c and miR-574. The level of errors in the differentiation of follicular adenoma and follicular cancer using the microRNAs we selected was 21 % (35 % with cross-validation).Conclusion. Molecular genetic research at the preoperative stage, aimed at differentiating follicular cancer and follicular adenoma, in comparison with cytological research has a greater, but insufficient accuracy for making a final clinical decision.